Zinc(II)-Catalyzed Synthesis of Secondary Amides from Ketones via Beckmann Rearrangement Using Hydroxylamine-O-sulfonic Acid in Aqueous Media - Verma, Saumya; Kumar, Puneet; Khatana, Anil K.; Chandra, Dinesh; Yadav, Ajay K.; Tiwari, Bhoopendra; Jat, Jawahar L. (Synthesis, 2020)
A zinc(II)-catalyzed single-step protocol for the Beckmann rearrangement using hydroxylamine-O-sulfonic acid (HOSA) as the nitrogen source in water was developed. This direct method efficiently produces secondary amides under open atmosphere in a pure form after basic aqueous workup. It is environmentally benign and operationally simple.
Keywords: zinc(II) chloride; hydroxylamine-O-sulfonic acid (HOSA); ketones; Beckmann rearrangement; amides